2022
DOI: 10.1192/bjp.2021.226
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mental health problems, coping self-efficacy and social support between adults victimised before and adults victimised after the COVID-19 outbreak: population-based prospective study

Abstract: Background Victims of violence, accidents and threats are at risk for mental health problems. Lower coping self-efficacy and social support levels increase this risk. Although highly relevant, it is unknown if the coronavirus disease 2019 (COVID-19) pandemic amplifies these risks. Aims To examine if the prevalence, incidence and/or mean scores for post-traumatic stress disorder (PTSD), anxiety and depression symptoms, general mental health problems, coping self-efficacy, lack of emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The most well-known models of social support are main effect and buffering effect models (Zaken et al, 2022), which provide evidence for the mechanism of occupational stress on job burnout. The main effect model holds that social support has a direct impact on individual work and health (van der Velden et al, 2022), which is consistent with the theory of JD-R model. According to the buffering effect model, social support can buffer the negative impact of stressful events on the physical and mental state of individuals, including burnout.…”
Section: Backg Rou N Dsupporting
confidence: 84%
“…The most well-known models of social support are main effect and buffering effect models (Zaken et al, 2022), which provide evidence for the mechanism of occupational stress on job burnout. The main effect model holds that social support has a direct impact on individual work and health (van der Velden et al, 2022), which is consistent with the theory of JD-R model. According to the buffering effect model, social support can buffer the negative impact of stressful events on the physical and mental state of individuals, including burnout.…”
Section: Backg Rou N Dsupporting
confidence: 84%
“…A previous longitudinal study using the LISS panel showed that adults exposed to potentially traumatic events (e.g. crime, accidents) during the first year after the outbreak more often suffered from ADS and probable PTSD than adults exposed to these events in a similar period before the outbreak ( Van der Velden et al, 2022c ). We did not include a subgroup of students (cf.…”
Section: Discussionmentioning
confidence: 97%
“…Centerdata received the CoreTrustSeal certification for the LISS Data Archive, based on the World Data System (WDS) of the International Science Council and the Data Seal of Approval (DSA) catalogue and procedures. As described above, this panel was also used in earlier mental health-related COVID-19 studies ( Van Tilburg et al, 2020 ; van der Velden et al, 2020 , van der Velden et al, 2021 , van der Velden et al, 2022a , van der Velden et al, 2022b , van der Velden et al, 2022c ).…”
Section: Methodsmentioning
confidence: 99%